2021
DOI: 10.1111/ecog.05253
|View full text |Cite
|
Sign up to set email alerts
|

Climate extreme variables generated using monthly time‐series data improve predicted distributions of plant species

Abstract: Extreme weather can have significant impacts on plant species demography; however, most studies have focused on responses to a single or small number of extreme events. Long-term patterns in climate extremes, and how they have shaped contemporary distributions, have rarely been considered or tested. BIOCLIM variables that are commonly used in correlative species distribution modelling studies cannot be used to quantify climate extremes, as they are generated using long-term averages and therefore do not descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…when compiled as ensembles and compared against separate climate datasets. The improvement is consistent with several recent studies showing how interannual variability in climate can improve SDMs(Karger et al, 2021;Perez-Navarro et al, 2021;Stewart, Elith, et al, 2021;Zimmermann et al, 2009). Importantly, this improvement was also found when using contrasting methodologies to produce temporal variation.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…when compiled as ensembles and compared against separate climate datasets. The improvement is consistent with several recent studies showing how interannual variability in climate can improve SDMs(Karger et al, 2021;Perez-Navarro et al, 2021;Stewart, Elith, et al, 2021;Zimmermann et al, 2009). Importantly, this improvement was also found when using contrasting methodologies to produce temporal variation.…”
supporting
confidence: 91%
“…All species data used in this study were presence and absence records obtained from systematic field studies within forested and woodland ecosystems. Species records were collated from multiple field campaigns to maximize the pool of available data points, including 1804 sites in Victoria (see Stewart, Elith, et al, 2021) and 349 sites in Bhutan (see Choden et al, 2021). The most prevalent canopy and understory plant species in each study region (38 in Victoria and 12 in Bhutan) were selected for modelling.…”
Section: Study Area and Species Datamentioning
confidence: 99%
See 1 more Smart Citation
“…glauca distributions are best predicted by the climate parameters yearly minimum and maximum temperatures, temperature range, temperature continentality, and spring precipitation. This suggests the importance of considering climate parameters beyond annual means, such as seasonal precipitation and climatic extremes (Stewart et al, 2021; Zimmermann et al, 2009). This is reflected in other Arctic studies, which have found plant responses to both climatic extremes and seasonal variables (Berner et al, 2020; Niittynen et al, 2020; von Oppen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, wet and cold aspects of the climate extreme were retrieved from the 95th percentile of precipitation and fifth percentile of temperature, respectively. Several recent studies also used the monthly climatic data to capture the climate extremes (Albright et al, 2011;Suggitt et al, 2011;Stewart et al, 2021).…”
Section: Change In Probability Of Local Climate Extremesmentioning
confidence: 99%